Strengthening financial management systems at primary health care: Performance assessment of the Facility Financial Accounting and Reporting System (FFARS) in Tanzania - Ruhago, George M.; Ngalesoni, Frida N.; Kapologwe, Ntuli A.; Kengia, James T.; Ngocho, James; Kabusi, Stephen M.; Kalolo, Albino; Kitali, Erick J.; Rwamiago, Elisa; Mtei, Gemini (Frontiers in Health Services, 2023)
Background Universal coverage remains a challenging pursuit around the world, even among the highest-income countries. Strengthening financial management capacity is essential towards attaining the three universal health coverage (UHC) goals, namely, expanded coverage, quality service, and financial protection. In this regard, Tanzania introduced the Facility Financial Accounting and Reporting System (FFARS) in line with the introduction of the Direct Health Facility Financing (DHFF) initiative in primary health care (PHC) in 2017–2018. We aim to assess the functionality of the FFARS in management, accounting, and reporting funds received and disbursed in the stride forward strengthening public financial management in PHC facilities towards UHC. Methods The study applied implementation research using a concurrent convergent mixed-methods design to assess sources of revenue, expenditure priorities, and changes of revenues and to explore the usability and benefits of FFARS in improving facility finance and reporting systems in more than 5,000 PHC facilities in Tanzania. Quantitative methods assessed the changes in revenues and expenditure between the financial years (FYs) 2017–2018 and 2018–2019, while the qualitative part explored the usability and the benefits FFARS offers in improving facility finances and reporting systems. Data analysis involved a thematic and descriptive analysis for qualitative and quantitative data, respectively. Results Of the 5,473 PHC facilities, 88% were in rural areas; however, the annual average revenue was higher in urban facilities in FYs 2017–2018 and 2018–2019. Overall, district hospitals showed an increase whereas health centers reported a decline of more than 40% in revenue. The user fee was the predominant source of revenue, particularly in urban facilities, while revenue from health insurance was not among the top three highest sources of revenue. Expenditure priorities leaned more towards drugs and supplies (25%) followed by allowances and training (21%); these did not differ by facility geographies. In health centers, expenditure on facility infrastructure was predominant. Key Informant Interviews revealed an overall satisfaction and positive experiences related to the system. Conclusion The implementation of FFARS in Tanzania demonstrated its high potential in improving facility financial management, including its ability to track revenue and expenditure at PHC facilities. Staffing shortages, ICT infrastructure, and limited opportunities for capacity building could be the limiting factors to reaching the potential of the implementation of FFARS and the attainment of its full impact on Tanzania's pursuit for UHC.